A comparison between the effects of degraded and non-degraded organic matters on the suppression of chickpea fusarium wilt caused by Fusarium oxysporum f. sp. Ciceris - Kamalaldeen M. Fatah; Majid H. Mustafa; Qasim A. Marzani (Zanco Journal of Pure and Applied Sciences, 2022)
A field study was conducted in Girdarasha research station, belongs to the College of Agricultural Engineering Sciences (CAES), Salahaddin University, Erbil Province, Kurdistan Region, Iraq. The objective was to investigate the effects of adding plant materials on the suppression of chickpea fusarium wilt disease caused by Fusarium oxysporum f. sp. ciceris. Two plant residues, fresh (non-degraded) and composted (degraded) from three plant sources of leaves were added to the soil. Eucalyptus (Eucalyptus camaldulensis), Dodonea (Dodonaea viscosa), and Neem (Azadirachta indica) were used as plant sources. Results showed the domination of composted matters over non-composted plant materials in their effects on the measured parameters (disease incidence, disease severity, plant height, and seed yield). Composted Eucalyptus leaves surpassed other composted residues in decreasing the disease severity. Nevertheless, the composted Dodonea leaves had the greatest effect in increasing both yield and plant height. The growth rate was an exception because it was not affected by the addition of these plant matters.